2002
DOI: 10.1055/s-2002-35635
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polycyano-Substituted Azulenes via Direct Oxidative Cyanation Reaction

Abstract: The synthesis of dicyano-, tricyano-, and tetracyanoazulenes substituted on both rings via direct oxidative cyanation reaction is described. 1-Cyanoazulene or 1,3-dicyanoazulene treated with tetraethylammonium cyanide (Et 4 N + CN -) and subsequently with DDQ or para-chloranil were transformed stepwise into the desired polycyano-substituted azulenes. Scheme 3Downloaded by: University of Pittsburgh. Copyrighted material.Counterion Et 4 N + (for both 9a, 10a): d = 3.02 (q, 2 H, J = 7.3 Hz, CH 2 ), 1.25 (t, 3 H, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The latter has a number of favorable consequences, including a low nucleophilicity and a weakly coordinating ability of the conjugate base anions. In this context, and since the chemistry of the cyano group is known, attempts to synthesize and prepare some of the acids proposed here are highly recommended.…”
Section: Resultsmentioning
confidence: 99%
“…The latter has a number of favorable consequences, including a low nucleophilicity and a weakly coordinating ability of the conjugate base anions. In this context, and since the chemistry of the cyano group is known, attempts to synthesize and prepare some of the acids proposed here are highly recommended.…”
Section: Resultsmentioning
confidence: 99%
“…Makosza et al reported the synthesis of 1-cyano-6-trimethylsilylethynylazulene (48) in 97% yield from 1-cyanoazulene (47) by firstly vicarious nucleophilic substitution (VNS) hydroxylation at 6-position to give 6-hydroxyazulene-1-carbonitrile followed by 6-O-sulphonylation to afford the corresponding trifluorome-thanesulfonate derivative and subsequent reaction with TMSA under Sonogashira conditions (Scheme 8). [46]…”
Section: Synthesis Of 6-ethynylazulenesmentioning
confidence: 99%